Antioxidant and anticancer activities of Plectranthus stocksii Hook. f. leaf and stem extracts - Muniyandi, Kasipandi; George, Elizabeth; Mudili, Vekataramana; Kalagatur, Naveen Kumar; Anthuvan, Allen Joseph; Krishna, Kadirvelu; Thangaraj, Parimelazhagan; Natarajan, Gopalan (Agriculture and Natural Resources, 2017)
The properties of Plectranthus stocksii-a well-known folk medicinal plant-were investigated. The plant extracts were successively extracted and tested for phytochemicals using high performance liquid chromatography, while antioxidant and anticancerous properties were assessed using MCF-7, Caco-2 and RAW264.7 cancerous cell line models. The methanolic extract of leaves showed higher concentrations of total phenolics (415.41 mg gallic acid equivalents/g extract) and tannins (177.53 mg gallic acid equivalents/g extract) contents than other studied extracts. In the case of flavonoids, ethyl acetate extract of leaf (LEA) showed a higher concentration (777.11 mg rutin equivalents/g extract) and was also found to have better antioxidant activity against stable radical 2,2-diphenylpicrylhydrazyl (3.46 mg/mL), 2,2'azinobis (3-ethylbenzothiozoline-6-sulfonic acid) disodium salt radical (27.41 mM Trolox equivalent/g extract) and superoxide (24.16 mg/mL) radicals and showed better IC50 (the concentration of the sample at which the inhibition rate reaches 50%) values on MCF-7 (48.874 mg/mL) and Caco-2 (36.088 mg/mL) cancerous cell line models. The immense anti-oxidant potential of P. stocksii leaf and stem extracts could be utilized as a good source of natural, anti-oxidant supplement in food to defend against oxidative-stress-related disorders and more generally in the food safety industry.